Financial Sustainability of KCIC Whoosh in the Ramp-Up Phase: A Narrative Review Based on IDX and Global HSR Benchmarks - Muhammad Rijal Alim Rahmat (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
The Jakarta Bandung High-Speed Rail (HSR), branded as Whoosh, entered commercial service in October 2023 as Indonesia’s first high-speed line. As a capital-intensive megaproject financed predominantly by long-term debt and implemented through a binational consortium, Whoosh presents a salient test case for financial management in complex transport infrastructure. This narrative review synthesizes peer-reviewed literature, official financial reports, governmental communications, and credible industry sources from 2023 through June 2025 to appraise the project’s evolving financial health through four core indicators: Debt Service Coverage Ratio (DSCR), Cash Flow Available for Debt Service (CFADS), Farebox Recovery Ratio (FRR), and Operating Ratio. The paper integrates conceptual frameworks from project finance and public private partnership (PPP) practice with empirical insights from global HSR benchmarks (Japan, China, the EU, and selected international cases) to interpret Whoosh’s early operating performance and capital structure. We find that initial years are characterized by high leverage, debt service pressure, and operating deficits that keep DSCR below unity, consistent with international experience in new HSR corridors. Yet by 2025, operational EBITDA reportedly turns positive and FRR approaches the break-even threshold, while public policy instruments most notably cash deficiency support and ongoing debt restructuring are mobilized to stabilize liquidity and improve solvency. The review argues that long-run financial sustainability will depend on simultaneous progress in three domains: revenue optimization (dynamic pricing, intermodal integration, and non-fare income), disciplined operating efficiency (energy, maintenance, asset utilization), and liability management (tenor extension, interest-cost relief, and calibrated equity reinforcement). We conclude with managerial and policy recommendations for safeguarding DSCR trajectories, strengthening CFADS growth, and aligning social objectives with financial viability.